(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Intensive production methods, the production and immeasurable consumption of meat, the use of fertilizers, the acidification of water, food waste, represent potentially suitable agents for determining the alarming climate change to which our planet is subjected. To this end, the regulations of recent years affect the rules of the agri-food chain, so as to offer an integral model of sustainability and circularity that can, to some extent, slow down climate change. There is a tendency towards a model capable of curbing the consequences of thinking about the present without looking to the future, of living without the conscious certainty that what is produced, thanks to and in the environment, returns to the latter, albeit, perhaps, in a different form.